Female is Associated with Left Ventricular Diastolic Dysfunction in Patients with Type 2 Diabetes [Response to Letter] - Wang Y; Zhou Y; Zhang Y; Ren Q; Wang Y; Su H (Diabetes, Metabolic Syndrome and Obesity, 2023)
Yiting Wang,1,* Yikun Zhou,1,* Yonghong Zhang,1 Qiuting Ren,2 Yan Wang,2 Heng Su1 1Department of Endocrinology and Metabolism, The First People’s Hospital of Yunnan Province, The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People’s Republic of China; 2Echocardiogram Laboratory, Department of Cardiology, The First People’s Hospital of Yunnan Province, The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Wang; Heng Su, Email ayisa_wang@aliyun.com; su_hen@hotmail.com